(untitled) (Research, Society and Development, 2022)
The Covid-19 pandemic imposed a reconfiguration in teaching, as a measure to mitigate the contagion and transmissibility of the disease, promoting the transition from face-to-face to remote teaching. Teachers had to learn to work from home without prior preparation. The study aimed to understand the experience of teaching women in remote work in the pandemic. This is a systematic review of the literature on female teaching work in higher education institutions (HEIs) and the pandemic context in the light of the Mental Burnout Theory. In the initial search using the descriptors, 83 scientific articles were found, of which 70 articles were excluded and 13 studies were selected. They contemplated the teaching work as an object of study linked to another theme corresponding to the knowledge area, only 04 addressed the experience and challenges of teaching women in the pandemic context. This corroborates the need to produce studies dealing with this little-observed reality, in order to think about public policies for the protection and support of working women.